Development of disease resistant bread wheat (Triticum aestivum) line in background of PBW 343 and genetics of Karnal bunt free trait - NAVTEJ SINGH BAINS; INDU SHARMA*, RITU BALA, SATISH KUMAR (Indian Phytopathology, 2015)
The KBRL 57, a Karnal bunt (KB) free stock of wheat (Triticum aestivum L.) was developed from a cross between Aldan and H567.71. Both lines are resistant to KB disease. This stock was used as a donor to introgress the KB resistance into PBW 343, the most widely-grown wheat cultivar in India. The introgression was done using conventional backcrossing method along with artificial inoculation with KB fungus. The KB-free and KB-affected plants in each backcross generation as well as F2, was recorded after artificial inoculation. The segregation of lines into KB - free and KB - affected in all the generations clearly indicated two independently segregating, dominant genes which jointly confer the KB resistance.